Comparison between the subgrade resilient module determined in the laboratory and retrocaculated adjustment factor C - Guzmán-Suárez, Edwin Antonio (Universidad Santo Tomás Seccional Tunja, 2016)
The main objective of this article is to understand the relationship between the Subgrade Resilient Retrocalculated Module (Mrr), given from the information provided by the Impact Deflectometer (FWD), and that obtained from the lab results (Mr), which is given by the designated adjustment factor “C”. Initially, a structural evaluation of a length of flexible pavement was analyzed through FWD. The results characterized the resistance of the subgrade through the Resilient Module parameter. Using retro calculation techniques, the values of the Resilient Module determined in the laboratory tests were compared. This yielded an adjustment factor in order to make the module values obtained comparable. The analysis consisted of retrocalculating the Resilient Module in the subgrade through the implementation of different methods. Then, these results were compared to the results obtained from the Resilient Module in the laboratory determined under the conditions prevailing in the pavement structure in service. As a result of the correlation found, the variables Mrr y Mr were established. The analysis yielded the conclusion that there exists more than one factor to be applied on the Resilient Module of the retrocalucated subgrade. Also, the adjustment factor depends on the method which categorizes the resistance of the subgrade and the Resilient Module equation of the subgrade material tested in the laboratory.